Mechanical behavior prediction of carbon fiber-reinforced Onyx in FDM using integrated statistical and machine learning approaches - Lavanya, D.; Guna, A. G. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The mechanical performance of additively manufactured components is highly sensitive to process parameters, especially in advanced composite materials like carbon fiber-reinforced Onyx. This study presents a comparative optimization framework combining Response Surface Methodology (RSM) and machine learning (ML) to model and enhance the tensile and flexural strengths of Fused Deposition Modeling (FDM) printed Onyx composites. Key parameters including infill pattern, infill density, and nozzle temperature—were systematically varied using a Taguchi L9 design, and mechanical testing was performed according to ASTM standards. Statistical analysis revealed infill pattern as the most significant factor affecting strength properties. RSM provided reliable predictions with R² values of 97.61% (tensile) and 95.93% (flexural), while ML models, particularly XGBoost coupled with Bayesian optimization, achieved superior prediction accuracy with zero average error. Both methods converged on the same optimal parameters hexagonal infill, 60% infill density, and 265 °C nozzle temperature highlighting the consistency and robustness of the integrated approach. The results demonstrate that combining traditional statistical methods with advanced machine learning offers a powerful pathway for precise process control and mechanical optimization in polymer composite additive manufacturing.

Адитивне виробництво (AM), широко відоме як 3D-друк, принесло значні зміни у виробничий сектор, дозволивши виробляти високоскладні геометрії з мінімальними матеріальними відходами та більшою гнучкістю дизайну. Серед різних технологій AM моделювання плавленого осадження (FDM) стало особливо популярним методом, в основному завдяки його економічній ефективності, доступності та сумісності з широким спектром термопластів. Нещодавні досягнення в галузі FDM призвели до появи армованих вуглецевим волокном ниток, таких як Onyx, які поєднують легку природу полімерів із підвищеною механічною міцністю та жорсткістю, розширюючи застосування FDM у таких секторах, як аерокосмічна, оборонна промисловість та структурні компоненти. Механічні характеристики компонентів, виготовлених за допомогою добавок, дуже чутливі до параметрів процесу, особливо в передових композитних матеріалах, таких як армований вуглецевим волокном онікс. У цьому дослідженні представлена порівняльна оптимізація, що поєднує методологію реагувальної поверхні (RSM) і машинне навчання (ML) для моделювання та підвищення міцності на розтяг і вигин композитів Onyx, надрукованих методом плавленого осадження (FDM).
Прогнозування механічної поведінки оніксу, армованого вуглецевим волокном, у FDM з використанням інтегрованих статистичних підходів і підходів машинного навчання
Keywords: additive manufacturing; carbon fiber reinforced Onyx; fused deposition modeling; machine learning; mechanical optimization; response surface methodology; XGBoost; адитивне виробництво; онікс; армований вуглецевим волокном; моделювання плавленим осадженням; машинне навчання; механічна оптимізація; методологія поверхні реагування; XGBoost